FaÃ¡liyah al-Tadribat 'ala Asas Maharat al-Tafkir al-Ãšlya fi Taâ€™lim al-QiraÃ¡h al-Ãrabiyyah - Mardiyah, Tika; Machmudah, Umi; Rosyidi, Abdul Wahab (Arabiyatuna: Jurnal Bahasa Arab, 2021)
This study aimed to determine the effectiveness of using exercises based on higher-order thinking skills in teaching reading. The type of this research was quantitative using a pre-experimental design with one group pre-test post-test. The research samples were forty students from all students at the third level of Arabic Language Education Department at the State Islamic University of Tulungagung. Data analysis was carried out using the statistical program SPSS 22 with paired sample T-Test and N-Gain Score. The results of this study indicated the following: (1) the higher-order thinking skills applied in Arabic reading exercises included the analysis level, evaluation and creativity in the formats of multiple choice, essay, true and false, pairing, completion, and work questions; (2) The results showed that there was a difference between the results of the pre-test and post-test with a Sig (2-tailed) value of 0.00; T-count was lower than than T-table; and the N-Gain Score value was of 0.61. It indicated that the alternative hypothesis (H1) was accepted, and the exercise was at a moderately effective level. The finding of this research demonstrated that the exercises based on higher-order thinking skills were effective in improving studentsâ€™ thinking skills in teaching Arabic reading.